Prevalence of anti-TNF contraindications in Crohn's disease: A cross-sectional survey from the GETAID. Issue 10 (October 2022) - Amiot, Aurelien; Seksik, Philippe; Reimund, Jean-Marie; Nachury, Maria; Altwegg, Romain; Bourreille, Arnaud; Viennot, Stephanie; Fumery, Mathurin; Roblin, Xavier; Serrero, Melanie; Allez, Matthieu; Painchart, Claire; et al.
Summary: Background: The exact rate of contraindications to anti-TNF therapy and physician perspectives on treatment choices facing to anti-TNF contraindication, are poorly reported. Methods: A two-week cross-sectional study was conducted in 31 centres. Physicians completed a questionnaire for a total of 1, 314 consecutive outpatients with Crohn's disease, assessing each patient's potential contraindications to anti-TNF therapy, the choice of alternative therapy to anti-TNFs, and their preference in an unrestricted reimbursement setting. Results: Among the 1, 293 responses to the first item, 148 (11.5%) reported 32 absolute contraindications (2.5%) and 116 relative contraindications (9.0%) to anti-TNF therapy. When asked about their preference of alternative therapies in those cases with contraindications to anti-TNF, physicians chose ustekinumab and vedolizumab, 75.6% and 23.9%, respectively. In multivariable analysis, the choice of vedolizumab was the preferred choice for patients aged > 60 years with the L2 phenotype and the absence of perianal lesions. In a hypothetical setting of unrestricted reimbursement, anti-TNFs remained physicians' preferred first-line biological therapy choice for 78.2%. Conclusion: Anti-TNF contraindications occurred in up to 11.5% of patients with Crohn's disease. Physicians' choices for alternative therapy to anti-TNF relied on ustekinumab in 75.6% and vedolizumab in 23.9% of these cases. This choice was driven mainly by phenotypical criteria and age.